A comparative evaluation of oxygen mass transfer and broth viscosity using Cephalosporin-C production as a case strategy - Mishra P.; Srivastava P.; Kundu S. (My University, 2025)
The production of Cephalosporin-C (CPC) a secondary metabolite, using a mold Acremonium chrysogenum was studied in a lab scale Internal loop air lift reactor. Cephalosporin-C production process is a highly aerobic fermentation process. Volumetric gas-liquid mass transfer coefficient (k L a) and viscosity (η) were evaluated, during the growth and production phases of the microbial physiology. An attempt has been made to correlate the broth viscosity, η and volumetric oxygen transfer coefficient, k L a during the Cephalosporin-C production in an air lift reactor. The impact of biomass concentration and mycelial morphology on broth viscosity has been also evaluated. The broth exhibits a typical non-Newtonian fermentation broth. Rheology parameters like consistency index and fluidity index are also studied. © Springer 2005.